2017
DOI: 10.3393/ac.2017.33.3.93
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Bowel Preparation and the Adenoma Detection Rate in Screening Colonoscopy

Abstract: PurposeThe adenoma detection rate is commonly used as a measure of the quality of colonoscopy. This study assessed both the association between the adenoma detection rate and the quality of bowel preparation and the risk factors associated with the adenoma detection rate in screening colonoscopy.MethodsThis retrospective analysis involved 1,079 individuals who underwent screening colonoscopy at the National Cancer Center between December 2012 and April 2014. Bowel preparation was classified by using the Aronch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 31 publications
1
25
1
Order By: Relevance
“…Adequate bowel preparation can be expected to increase PDR and ADR during colonoscopy. However, several recent studies reported that PDR and ADR are not closely related to the quality of bowel preparation [18-20]. In our study, PDR and ADR were significantly lower in the SMM group than in the control group.…”
Section: Discussioncontrasting
confidence: 70%
“…Adequate bowel preparation can be expected to increase PDR and ADR during colonoscopy. However, several recent studies reported that PDR and ADR are not closely related to the quality of bowel preparation [18-20]. In our study, PDR and ADR were significantly lower in the SMM group than in the control group.…”
Section: Discussioncontrasting
confidence: 70%
“…Obesity has been strongly associated with precancerous lesions and conditions such as colon adenomas [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86], monoclonal gammopathy [87][88][89][90][91][92][93][94][95][96][97][98], chronic pancreatitis [99][100][101][102], or inflammatory bowel disease (IBD) [103][104][105][106]. Observed risks of cancers associated with obesity include breast [107][108][109][110][111], colorectal [112][113][114][115], pancreatic [99]…”
Section: Morbid Obesitymentioning
confidence: 99%
“…As a result, a proposal was recently made that the ADR be applied to patients older than 50 years of age. In the present study [ 3 ], age, body mass index, and smoking were factors associated with increased numbers of adenomas in the patients. In addition, prolonged observation time, observations during repeated insertions, changes in both the air volume and the position during observation, the use of a pigmented endoscope, and the use of a high-resolution electronic endoscope were factors associated with an increased ADR [ 4 ].…”
mentioning
confidence: 66%